Characterization of Rubber Bark (Hevea Brasiliensis) as s Raw Material and Fly Ash as a Catalyst for the Production of Biofuel - Fenoldi, Nova; Muhammad Yerizam; Kalsum, Leila (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The research conducted on the utilization of rubber wood bark biomass for biofuel production employs the pyrolysis process. Rubber wood bark, a by-product of rubber plantation waste, has the potential to be converted into energy. However, its utilization has not been optimal, often leading to accumulation issues due to its inability to be fully utilized. Therefore, this study aims to utilize rubber wood bark to produce biofuel. Fly ash catalyst is employed to expedite the biofuel production process. The testing methods used to analysis the characteristics of rubber wood bark include proximate analysis and calorific value analysis. Proximate analysis of rubber wood bark yielded the following values: moisture content of 6.39%, ash content of 4.61%, volatile matter of 71.41%, and fixed carbon of 17.59%. The calorific value of rubber wood bark was determined to be 4200.00 calories per gram. Meanwhile, the characteristics of coal fly ash used as a catalyst were analyzed using X-Ray Fluorescence (XRF) or X-ray diffraction. The analysis revealed the presence of silicon dioxide (SiO2) at 49.21%, aluminum oxide (Al2O3) at 16.22%, iron (III) oxide (Fe2O3) at 5.49%, calcium oxide (CaO) at 7.37%, magnesium oxide (MgO) at 1.72%, and potassium oxide (K2O) at 0.50%. The analysis of rubber wood bark and coal fly ash indicates that rubber wood bark can be used as a raw material for biofuel production, while coal fly ash can serve as a catalyst.